ANALISIS SALURAN PEMASARAN PRODUK SUSU BUBUK KEDELAI (Studi Kasus: Industri Sumber Gizi Nabati, Pekanbaru) - Shorea Khaswarina '; Evy Maharani '; Annisa Zada Nugroho (PEKBIS, 2015)
This study aims to analyze the efficiency of marketing channels product soybeanmilk. Research location named Industri SGN at Seminai Ujung street, Pekanbaru.The method used is descriptive and analytical methods margin, profit, marketingefficiency and share price received by producent of the milk marketing. There aretwo marketing channels soy milk powder in the Industri SGN. Marketing agenciesinvolved in the first channel that the agent/distributor and a regular outlet, while inthe second channel the industry in cooperation only with the agent. The farmer’sshare in each channel is the same at 65,71% because the industry sells a product atthe same price. Marketing margin in the first and second channel each in theamount of Rp 12,000,-. Marketing efficiency in the first channel of 7,62%, while thesecond channels is equal to 11.14% and this channel is more efficient because thechannels is short and profit received by the agent is greater.Keywords: Marketing channels, marketing efficiency, and soybean